Excess mortality among Latino people in California during the COVID-19 pandemic. (September 2021) - Riley, Alicia R.; Chen, Yea-Hung; Matthay, Ellicott C.; Glymour, M. Maria; Torres, Jacqueline M.; Fernandez, Alicia; Bibbins-Domingo, Kirsten
Abstract: Latino people in the US are experiencing higher excess deaths during the COVID-19 pandemic than any other racial/ethnic group, but it is unclear which sociodemographic subgroups within this diverse population are most affected. Such information is necessary to target policies that prevent further excess mortality and reduce inequities. Using death certificate data for January 1, 2016 through February 29, 2020 and time-series models, we estimated the expected weekly deaths among Latino people in California from March 1 through October 3, 2020. We quantified excess mortality as observed minus expected deaths and risk ratios (RR) as the ratio of observed to expected deaths. We considered subgroups categorized by age, sex, nativity, country of birth, educational attainment, occupation, and combinations of these factors. Our results indicate that during the first seven months of the pandemic, Latino deaths in California exceeded expected deaths by 10, 316, a 31% increase. Excess death rates were greatest for individuals born in Mexico (RR 1.44; 95% PI, 1.41, 1.48) or a Central American country (RR 1.49; 95% PI, 1.37, 1.64), with less than a high school degree (RR 1.41; 95% PI, 1.35, 1.46), or in food-and-agriculture (RR 1.60; 95% PI, 1.48, 1.74) or manufacturing occupations (RR 1.59; 95% PI, 1.50, 1.69). Immigrant disadvantages in excess death were magnified among working-age Latinos in essential occupations. In sum, the COVID-19 pandemic has disproportionately impacted mortality among Latino immigrants, especially those in unprotected essential jobs. Interventions to reduce these inequities should include targeted vaccination, workplace safety enforcement, and expanded access to medical care and economic support. Highlights: During the first seven months of the pandemic, Latino deaths in California exceeded expected deaths by 10316, a 31% increase. Relative increases in mortality were greatest for Latinos born in Mexico or Central America, Latinos with less than a high school degree, and Latinos in food-and-agriculture or manufacturing occupations. Immigrants in essential occupations had the highest relative increase in death during the pandemic among working-age Latinos. Workplace exposure may be key contributor to the disproportionately high COVID-19 mortality experienced by Latinos in CA.